Pakistan: Country brief - HarvestPlus (International Food Policy Research Institute, 2015)
HarvestPlus aims to improve nutrition and public health in Pakistan by promoting wheat that can provide more zinc in the diet. We work with more than 20 partners drawn from government, business, and civil society.